Pengembangan Kurikulum Pencak Silat Berbasis Kerangka Kualifikasi Nasional Indonesia - Suandi Selian; Dodi Irwansyah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
This study aims to find the development of the pencak silat curriculum based on the Indonesian National Qualifications Framework, the specific target at this first stage is to analyze the needs of the pencak silat curriculum and the formation of the pencak silat curriculum based on the Indonesian National Qualifications Framework and also based on the competencies expected from Permenpan RB. The research methodology used was the development research (R&D) Borg & Gall. the sample in this study were students and lecturers of Pencak Silat course at the Sports Study Program of Universitas Samudra Langsa. Based on the research objectives, to form graduates who have the competence to become professional teachers in the field of martial arts studies so that they can compete with graduates both from domestic and abroad. In the First Stage planned activities in the form of observation, interviews and comparative studies to study programs that have run the Indonesian National Qualifications Framework based curriculum, and produce a draft curriculum framework. Then in the second phase based on the results of the draft drafts conducted Focus Group Discussion on curriculum experts, pencak silat experts and lecturers in the field of Pencak Silat Expertise Field so that the formation of a validated curriculum, in the third stage a trial was conducted for Sports Study Program students, Teaching Faculty and Education Sciences, Universitas Samudra Langsa and evaluated.